PELAKSANAAN EKSTRAKURIKULER SENI TARI DI SMAN 1 LENGAYANGKECAMATAN LENGAYANG KABUPATEN PESISIR SELATAN - Aisyah Dwi Sofiani; Ayuthia Mayang Sari (Universitas Negeri Padang, 2025)
This study aims to understand and describe how the implementation process of dance extracurricular activities is conducted at SMAN 1 Lengayang, Lengayang District, South Coastal Regency. This research uses a qualitative approach with a descriptive method. The research instrument is the researcher themselves, assisted by writing tools and a camera. Data is collected through literature study, observation, interviews and documentation. The steps of data analysis are data collection, data reduction, data presentation and drawing conclusions. The results of the study show that dance extracurricular activities at SMAN 1 Lengayang, Lengayang District, South Coastal Regency consist of program planning, activity implementation and evaluation. The planning of extracurricular dance activities at SMAN 1 Lengayang, Lengayang District, South Coast Regency has been well organised and in accordance with the plan made by the mentor. The schedule and objectives of the activities have also been clearly determined and carried out on time. The implementation of the dance extracurricular activities went well. The mentor tried their best to ensure that students could practice according to the set schedule and location. However, there are still challenges due to inadequate facilities and infrastructure, which slightly hinder the training process. Evaluation results show an improvement in students' abilities from the first to the third meeting. The mentor showed appreciation by presenting students' dance performances at the school's guest reception event, which then encouraged students to continue practising and developing their skills.